Podocyte autophagic activity plays a protective role in renal injury and delays the progression of podocytopathies. Issue 2 (4th August 2014) - Zeng, Caihong; Fan, Yun; Wu, Junnan; Shi, Shaolin; Chen, Zhaohong; Zhong, Yongzhong; Zhang, Changming; Zen, Ke; Liu, Zhihong
Abstract The progression of podocytopathies is quite variable among patients and the underlying reason for this remains unclear. Here, we report that autophagic activity in podocytes plays a critical role in controlling the progression of podocytopathies. Morphological and biochemical studies on renal biopsies from patients with minimal change disease (MCD) or focal segmental glomerulosclerosis (FSGS) showed that glomeruli, and in particular podocytes, from MCD patients had higher levels of Beclin1‐mediated autophagic activity than glomeruli from FSGS patients. Repeat renal biopsies of MCD patients enabled tracking of podocyte autophagic activity and confirmed that patients maintaining high podocyte autophagic activity retained MCD status, whereas patients with decreased podocyte autophagic activity progressed to FSGS. Inhibition of autophagic activity, by knocking down Beclin1 or by treating with 3‐methyladenine (3‐MA) or chloroquine, enhanced puromycin aminonucleoside (PAN)‐induced apoptosis of podocytes. In contrast, rapamycin‐mediated promotion of autophagic activity decreased this apoptosis. In PAN‐treated rats, inhibition of autophagy with 3‐MA or chloroquine resulted in earlier onset and greater proteinuria, more extensive foot‐process effacement, and reduction in podocyte markers, whereas rapamycin‐mediated stimulation of autophagy led to decreased proteinuria and less severe foot‐process effacement, but higher expression of podocyte markers. This study demonstrates that podocyte autophagic activity plays a critical protective role in renal injury and that maintaining podocyte autophagic activity represents a potential therapeutic strategy for controlling the progression of podocytopathies. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd